Numerical Evaluation of Heat Recovery Performance of a Switchable Exhaust Air Window. (June 2016) - Zhang, Chong; Cheng, Kuang; Wang, Jinbo; Xu, Xinhua
Abstract: Switchable exhaust air (SEA) window allows the exhaust air from HVAC system to be ventilated through the cavity of the window to ambient. It can be regarded as an exhaust air heat recovery device in buildings. The annual energy requirement of the window has been calculated in Wuhan, China. The energy requirements for conditioning fresh air with and without the total heat recovery ventilators (THRVs) are also investigated. Heat recovery performance of the SEA window and the THRVs is compared. Results show that the SEA window can potentially provide alternative solution for recovering the low-grade energy from air-conditioning exhaust air.